ANALYSIS OF MATHEMATICAL MODELS OF ADJUSTING OF OFFICE HOURS OF THE DIFFICULT GAS-TRANSPORT SYSTEMS - Тимків, Дмитро Федорович; Онацко, Р. Г.; Матієшин, Дмитро Дмитрович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
In the article the mathematical models of work of the difficult gas-transport systems and expedience of their use are analyzed for the optimum management by the operating modes of gas pipelines.